(3GdbhejI h JYHjQGJgG YfO GdeUQi GdbOje MJi fgGjI GdJGQjN GdeUQi GdbOje (B: s (3OQGSI dZhjI(B-(3MVGQjI (B/ s - (3fLdGA aJMj CMeO TgGHs; (3YdG GdYLjRi (B: s; (3eMeO UdGM GdNhdi (B: s ((3GdbGgQI (B: s (3fLdGA aJMj CMeO TgGH (B: s, 2012)
(3GdCSHGH GdJi Jcef hQGA HbGA GdMVGQI GdeUQjI GdJi GSJeQJ SHYI GdBa YGeB eG Hjf aJQGJ EROgGQ h cHhGJ MJi hbJfG GdMGdi ? h Edi Ci eOi JhGaQJ ebheGJ GdbhejI ai eUQ GdbOjeI ? h Edi Ci eOi dYH GdOjf OhQB ai ERcGA GdQhM GdbhejI? h cja HQR GdTYhQ Gdbhej ef NdGd GdfhGMi GdKbGajI h GdSjGSjI h GdCOHjI dOi GdUQi GdbOje ?? h eGgi eYhbGJ GdbhejI ai eUQ GdbOjeI ?? Ke JfGhdJ GdOQGSI eaghe GdbhejI h eOdhdGJ GdcdeGJ GdJi JQJHW HgG h ebheGJ GdbhejI Ke Je JfGhd OQGSI YhGed GdbhejI h eOi JhGaQgG ai eUQ GdbOjeIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBKGQ (B- (3bSe GdBKGQ GdeUQjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3CSeGA eUQ h GdeUQjjf GdbOeGAs; (3ebheGJ GdbhejIs; (3fXQI GdeUQi ddCLfHis